Peran Pelatihan Keterampilan dan Kesempatan Kerja terhadap Kemandirian Ekonomi Penyandang Disabilitas di Surabaya - Asjari, Fachrudy; Suwarno, Yuniar Fintari Gatrassia; Rahmawati, Dias; Almunawaroh, Silvi Anita; Lestari, Yunita Dewi (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the role of skills training and employment opportunities in increasing the economic independence of people with disabilities in Surabaya. People with disabilities often face difficulties in accessing decent work. Therefore, improving skills is very important to strengthen labor market capabilities. This research uses literature review techniques to examine various studies, reports and policies regarding disability qualifications and workforce integration. This research uses literature review techniques to examine various studies, reports and policies regarding disability qualifications and workforce integration. Research shows that training that suits the needs and potential of people with disabilities has a significant impact on their economic independence. In addition, inclusive employment opportunities in both the formal and informal sectors are an important element in encouraging the active participation of people with disabilities in economic activities. This study highlights the importance of government, training institutions and the private sector working together to build an inclusive work ecosystem and support economic independence for people with disabilities.